Development of AQDA Learning Media Based on Google Sites to Improve Learning Outcomes of Class X Students - Miftakhul Choiriyah; Iin Baroroh Ma’arif (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to (1) determine the development of AQDA learning media based on Google Sites (2) determine the effectiveness of using AQDA learning media in improving the learning outcomes of class X students of MA Unggulan K.H. Abd. Wahab Hasbulloh Tambakberas Jombang (3) determine the response of class X students to the use of AQDA media. The method used in this study is the Research and Development (R&D) research method developed using the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. The resulting product is validated by material experts and media experts to determine the feasibility of the learning media before being tested. The results of this study obtained a material validation score of 90% and a media validation of 92%, which means that this learning media is categorized as